A highly fluorescent PN-heterocycle-fused pyrene derivative with strong self-dimerisation through hydrogen bonding. Issue 1 (2nd January 2020) - Bard, Jeremy P.; Mancuso, Jenna L.; Deng, Chun-Lin; Zakharov, Lev N.; Johnson, Darren W.; Haley, Michael M.
ABSTRACT: The pyrene moiety has been utilised in a variety of systems that exhibit either 'turn on' or 'turn off' fluorescence in response to specific analytes. Continued development of hydrogen bonding pyrene-containing scaffolds seeks to establish a wider substrate scope and utility of these hosts. Herein, we report one such example in the form of a pyrene-containing phosphaquinolinone. This molecule exhibits both strong dimerisation in the solution state and π–π stacking within the pyrene backbone in the solid state. Further, it shows an enhanced quantum yield (70%) and a large extinction coefficient compared to its parent framework. Graphical abstract: